The concept of evaluativeness in the understanding of domestic and foreign linguists - Babenko E. A., Fomina A. R. (Socio-Pedagogical Issues of Education and Upbringing, 2022)
The article considers the category of evaluation, analyzes various approaches to the interpretation of the concept of "evaluation". The authors of the article consider the components of the evaluation structure, distinguish between descriptive and evaluative meanings of words, analyze dictionaries of the evaluative vocabulary of the Russian language.
Keywords: оценка; evaluation; категория оценочности; оценочный компонент значения; словари оценочной лексики; структурные компоненты оценки; evaluation category; evaluation component of value; evaluation vocabulary dictionaries; structural components of evaluation